(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
We want to demonstrate that Apollonia of Cyrenaica was neither an independent foundation, nor a real sub-colony, rather a maritime stopover: “the harbor of Cyrene”, where port and military installations were located; inhabited between the Archaic and Hellenistic periods by merchants and artisans, garrisons and seafaring staff. Following its civic development is of great interest: frequented by members of the Alexandrian court, it became an autonomous polis with its own institutions at the moment of the passage under the Roman domination, then it rises to capital of the Libya superior in the mid-fourth century A.D., and as such became also an object of imperial munificence. Despite moments of disagreement, it will never completely lose its privileged connection with Cyrene.